Peran Guru dalam Mengatasi Kesulitan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam (PAI) di SD Negeri 1 Jaya Bakti - Moh. Yahya Obaid; Masdin Masdin; Hadi Machmud; Waode Yunita (IAIN Kendari, 2021)
The purpose of this study was to examine the portrait of learning difficulties experienced by fourth grade students in the subject of Islamic Religious Education (PAI) at SD Negeri 1 Jaya Bakti and to examine the role of teachers in overcoming these learning difficulties. This research employed qualitative research with interviews, observations, and documentation as data collection techniques. Data analysis was carried out through data reduction, data presentation and data verification. The validity of the data was tested through extended observations, increased persistence, and triangulation techniques. The results showed that the forms of learning difficulties of students in Islamic Religious Education (PAI) class IV SD Negeri 1 Jaya Bakti were lack of student motivation, slow to learn, and unable to learn. The teacher's role in overcoming students' learning difficulties in Islamic Religious Education (PAI) class IV at SD Negeri 1 Jaya Bakti is that the teacher becomes a facilitator and good role model for students and creates fun learning.Keywords: Teacher’s Role, Learning Difficulties, PAI Learning